2020
DOI: 10.3390/land9120518
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationships between Extensive Livestock Systems, Land-Cover Changes, and CAP Support in Less-Favored Mediterranean Areas

Abstract: Farm abandonment and over-extensification trends in less-favored livestock breeding areas in the Mediterranean have led to socio-environmental issues that are difficult to assess and address, due to the characteristics of these areas (e.g., poor data availability and reliability). In a study case that presents many of the characteristics common to these areas, we combine qualitative and quantitative approaches to assess (i) the relationship between livestock production and land-cover change and (ii) the driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This means allowing farmers to reduce the production costs of pen building and feed provision, increasing earnings, and facilitating care. However, Delattre et al (2020) and Gaona et al (2021) reported that the weakness of an extensive livestock system is the requirement for an ample supply of input to maintain good livestock productivity. An extensive care system also tends to increase the risks of caring for and spreading diseases (Temple and Manteca 2020;Delsart et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This means allowing farmers to reduce the production costs of pen building and feed provision, increasing earnings, and facilitating care. However, Delattre et al (2020) and Gaona et al (2021) reported that the weakness of an extensive livestock system is the requirement for an ample supply of input to maintain good livestock productivity. An extensive care system also tends to increase the risks of caring for and spreading diseases (Temple and Manteca 2020;Delsart et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For selecting livestock production systems, many categorizations exist in the literature. For example, intensive (Ilea, 2009) and extensive (Delattre et al, 2020) livestock farming, precision livestock farming (Hartung et al, 2017), multispecies livestock farming (Martin et al, 2020), and integrated crop‐livestock farming (Moraine et al, 2014) are represented. These categories are not, however, based on any regulatory indicators and are mostly defined for individual studies, fitting the research purpose and setup.…”
Section: Methods and Datamentioning
confidence: 99%
“…In most cases, these dynamics are identified through land use and land cover change analysis (e.g. Bajocco et al, 2012;Delattre et al, 2020;Kefalas et al, 2019;Marraccini et al, 2015), whereas land use management and spatially-explicit information about agricultural and farming practices are seldom considered, even though they are relevant to understand the actual impact on ecosystem services, instead of the potential one (Rizzo et al, 2019;Temme and Verburg, 2011). Moreover, there are still some gaps of knowledge on how divergent development trajectories act on the same areas (Debolini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%